Revascularization for patients with diabetes mellitus and stable ischemic heart disease: an update. (September 2017) - Mancini, G.B. John; Farkouh, Michael; Verma, Subodh
Abstract : Purpose of review: To provide an update on the management of patients with diabetes mellitus and requiring coronary revascularization. Recent findings: Evidence continues to show that patients with diabetes mellitus and ischemic heart disease represent a very high-risk group of patients. Choice of stent appears important for minimizing target lesion and target vessel adverse events with everolimus eluting stents having the best performance, particularly in patients being treated with insulin. The higher risk of adverse angioplasty results in patients with diabetes appears most related to the disease state per se and not necessarily to anatomical complexities. Interestingly, physiologic documentation of nonischemia producing lesions with use of fractional flow reserve appears less reassuring in this setting of aggressive and rapid atherosclerosis progression, particularly if myocardial infarction has occurred previously, than in patients without diabetes. Coronary artery bypass surgery in patients with appropriate anatomy and diabetes continues to emerge in many analyzes as the optimal, long-term therapy. Implications: The treatment of diabetes per se, advances in stent technology and optimization of coronary artery bypass techniques are all occurring in parallel making it very critical for the design of modern era trials that keep pace with these advances. Currently, in patients with appropriate anatomy who are willing candidates, bypass surgery remains the optimal, long-term therapeutic option.